Comparative steam bending characteristics of some planted forest wood species in Malaysia - Ratnasingam, Jegatheswaran; Ab Latib, Hazirah; Lim, Choon Liat; Farrokhpayam, Saeid Reza (North Carolina State University, 2022)
The bending performance of wood is important for its application in furniture, and it is one of the criteria used to assess the suitability of a particular wood species for furniture. In this context, the steam-bending and surface roughness characteristics of four forest plantation wood species were evaluated. One batch of wood specimens were subjected to both surface roughness experiments using the stylus and toluene spread methods, while another batch of the wood specimens were subjected to steaming, clamped, and bent using a circular shape mold. The instantaneous spring-back was measured after 10 days, while the spring-back over time was measured from days 15 to 65. The surface roughness experiments showed that the Hevea brasiliensis had the lowest surface roughness, followed by the Eucalyptus pellita, Acacia mangium, and finally Revotropix paulownia. In terms of the bending performance, it was found that only the H. brasiliensis achieved the threshold 95% satisfactory level based on visual ranking. Furthermore, the wood species also recorded the lowest spring-back, both instantaneous and over-time, to register the best bending performance. On the other hand, R. paulownia had the worst bending performance, primarily due to its low density.